Morphologic Evaluations of Hypoglossal Canal using Cone Beam Computed Tomography - Duman, Suayip Burak; Seyrek, Mehmet; Yasa, Yasin; Gumussoy, Ismail; Dedeoglu, Numan; Bayrakdar, Ibrahim Sevki (Univ Kebangsaan Malaysia, 2021)
Hypoglossal canal (HC) which begins from very slightly above the inner part of the anterolateral portion of the foramen magnum and is located above the occipital condyle of the occipital bone. The aim of this study is to examine HC morphology and variations using cone beam computed tomography (CBCT). The morphology and types of HC were investigated with 303 CBCT images (606 side). type 1 variation in 606 HC examined becomes the most commonly observed type (57.3%) while type 5 variation was the least common type of variation (0.8%). Type 1 BC was statistically higher in males (p=0.004). Because of HC, which is an anthropologically important point and enters the field of images in CBCT scan, it is recommended that dental radiologists should be aware of their variations and be wary of the pathologies that may occur in this region.
Penilaian morfologi saluran hipoglosus menggunakan tomografi pemancaran kon berkomputer
Keywords: CBCT; foramen magnum; hypoglossal canal; occipital condyle